Optimalisasi Penguatan Kompetensi Guru Bimbingan dan Konseling Melalui Pelatihan Pembuatan RPLBK Berbasis Four C’s - Silvia AR; Nur Wisma; Alrefi; Riski Novirson (JPM: Jurnal Pengabdian Masyarakat, 2025)
The increasingly complex demands of the modern era require educational services, including guidance and counseling, to transform and align with the needs of 21st-century learners. School counselors play a strategic role in guiding students to develop their potential and plan their future careers effectively. However, a needs assessment conducted in Ogan Ilir Regency revealed that many school counselors still face challenges in designing Counseling Service Implementation Plans (RPLBK) based on 21st-century skills, known as the Four C’s: Critical Thinking, Creativity, Collaboration, and Communication. This community service activity aimed to enhance the professional competence of school counselors through a structured training program focused on developing RPLBK aligned with the Four C’s framework. The training was delivered using a blended learning model with an in-on-in approach, including theoretical sessions, face-to-face workshops, and follow-up mentoring for revision and evaluation. The evaluation results indicated a significant improvement in participants’ understanding and skills in designing more creative, collaborative, and contextually relevant RPLBKs. This initiative is expected to serve as a starting point in strengthening the professional capacity of school counselors to provide adaptive and relevant career guidance services in the digital era.